Efficient removal of perfluorooctane sulfonate from aqueous film-forming foam solution by aeration-foam collection. (July 2018) - Meng, Pingping; Deng, Shubo; Maimaiti, Ayiguli; Wang, Bin; Huang, Jun; Wang, Yujue; Cousins, Ian T.; Yu, Gang
Abstract: Aqueous film-forming foams (AFFFs) used in fire-fighting are one of the main contamination sources of perfluorooctane sulfonate (PFOS) to the subterranean environment, requiring high costs for remediation. In this study, a method that combined aeration and foam collection was presented to remove PFOS from a commercially available AFFF solution. The method utilized the strong surfactant properties of PFOS that cause it to be highly enriched at air-water interfaces. With an aeration flow rate of 75 mL/min, PFOS removal percent reached 96% after 2 h, and the PFOS concentration in the collected foam was up to 6.5 mmol/L, beneficial for PFOS recovery and reuse. Increasing the aeration flow rate, ionic strength and concentration of co-existing surfactant, as well as decreasing the initial PFOS concentration, increased the removal percents of PFOS by increasing the foam volume, but reduced the enrichment of PFOS in the foams. With the assistance of a co-existing hydrocarbon surfactant, PFOS removal percent was above 99.9% after aeration-foam collection for 2 h and the enrichment factor exceeded 8400. Aeration-foam collection was less effective for short-chain perfluoroalkyl substances due to their relatively lower surface activity. Aeration-foam collection was found to be effective for the removal of high concentrations of PFOS from AFFF-contaminated wastewater, and the concentrated PFOS in the collected foam can be reused. Graphical abstract: Highlights: PFOS removal reached 96% after 2 h with an aeration flow rate of 75 mL/min. PFOS enrichment factor exceeded 8400 with the assistance of APG. High ionic strength accelerated the PFOS removal by aeration-foam collection. Aeration-foam collection is suitable for PFOS recovery from AFFF wastewater.